Present and future flooding and erosion along the NW Spanish Mediterranean Coast - Sánchez-Artús, Xavier; Gracia, Vicente; Espino, Manuel; Sierra, Joan Pau; Pinyol, Jordi; Sánchez-Arcilla, Agustín (Frontiers in Marine Science, 2023)
Coastal flooding and erosion caused by extreme events are the main responsible for beach. This effect will be exacerbated by the sea level rise induced by climate change. The present work determines the vulnerability to erosion and flooding along 55 beaches grouped in different coastal archetypes, representative of the Catalan coast. The vulnerability assessment has been done through the numerical simulation of different combinations of projected waves and mean water levels for RCP8.5 climate change scenario for the year 2100. A storm event approach has been used to determine coastal flooding and erosion with return periods of 50, 100 and 500 years using the XBeach numerical model. Results show that shoreline retreat is not a good proxy to characterise the erosion. The low-lying nature of the coast and the existence of river mouth and torrents govern the coastal flooding. The sea level rise appears to be a dominant variable in the coastal hazards.